The Effect of Work Stress and Workload on the Performance of Employees in the NBC/Biscuit Division at PT Mayora Indah Tbk - Afiah, Tia; Hia, Era Era; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the simultaneous influence of job stress and workload on employee performance in the NBC/Biscuit division at PT Mayora Indah Tbk.This study employed a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all NBC/Biscuit division at PT Mayora Indah Tbk. The sample size was 62 respondents. This study used a saturated sampling technique due to the small population size; therefore, the entire population (62 employees) was used as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis using SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, work stress significantly influences the performance of NBC/Biscuit employees at PT Mayora Indah Tbk, as indicated by the calculated t value > t table (2.209 >1.990) and a significance value of 0.000 smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (2) Partially, workload significantly influences the performance of NBC/Biscuit employees at PT Mayora Indah Tbk, as indicated by the calculated t value > t table (10.024 >1.990) and a significance value of 0.000 smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (3) Simultaneously, work stress and workload significantly influence the performance of NBC/Biscuit employees at PT Mayora Indah Tbk, as indicated by F count > F table (334.900 >3.11) with a significance level of 0.000. Thus, Ha is accepted and H0 is rejected.Based on the research results, it can be concluded that the variables of work stress and workload, both partially and simultaneously, have a significant influence on the performance of NBC/Biscuit employees at PT Mayora Indah Tbk.